L’oubli du patrimoine - Stéphane Olivesi (Communication)
The study looks at people’s relationship to local heritage, the conditions for transmitting memory, the relationship between identity and place, and the reasons why the past is or is not the object of a symbolic appropriation, inhabits our memories in various forms, and is either given value and passed down or else neglected, forgotten, or obscured. Rather than analyzing an established process of heritage-making, the author examines the flip side of the coin, when heritage does not get made. The ethnographic survey is based on both biographical and mnesic sources and contemporary data collected through observation, documentation, and interviews. It focuses on showing that behind every person’s relationship to the past lies the shadow of history